Dating the Gaofan and Hutuo Groups – Targets to investigate the Paleoproterozoic Great Oxidation Event in North China. (1st May 2017) - Peng, Peng; Feng, Lianjun; Sun, Fengbo; Yang, Shuyan; Su, Xiangdong; Zhang, Zhiyue; Wang, Chong
Graphical abstract: Highlights: Felsic tuff in the Mohe Fm. (Gaofan Group) gives a ∼2190 Ma zircon U-Pb age. The Banlaoyao sill in the Dongye Subgroup gives a ∼2060 Ma zircon U-Pb age. The deposition age of the Gaofan Group was confined to 2350–2150 Ma. The Doucun-Dongye Subgroups of the Hutuo Group deposited at 2150–2060 Ma. The Gaofan-Hutuo Groups in North China recorded the Great Oxidation Event. Abstract: There are several sedimentary units in North China that are proposed to be associated with the Paleoproterozoic Great Oxidation Event (GOE) and/or subsequent events; however, few of them have been precisely dated. In this study, deposition age of the greenschist facies Gaofan and Hutuo Groups is determined. Zircon grains liberated from a tuff layer (metamorphosed to sericite-quartz schist) in the upper part of the Mohe Formation (the second of the three formations of the Gaofan Group) yield a weighted average 207 Pb/ 206 Pb age of 2186 ± 8 Ma (n = 7, MSWD = 1.3), representing time of deposition. This age and the detrital zircon U-Pb ages of the basal feldspar quartzite (meta-siltstone), as well as the initial deposition age of the unconformably overlying Hutuo Group, confine the deposition age of the Gaofan Group to 2350–2150 Ma. This result negates the Gaofan Group as one subgroup of the 2560–2510 Ma Wutai greenstone belt. Zircons from the Banlaoyao mafic sill (meta-diabase) that intruded the Dongye Subgroup of the Hutuo Group yield an upper intercept U-Pb age of 2057 ± 25 Ma (n = 14, MSWD = 1.3), representing time of crystallization. Considering the age of the basalt in the first formation of the Doucun Subgroup and the tuff in the first formation of the Dongye Subgroup, the deposition age of the Doucun and Dongye Subgroups of the Hutuo Group is confined to 2150–2090 Ma and 2090–2060 Ma, respectively. These age brackets, as well as the available carbon and nitrogen isotope data indicate that the Zhangxianbu Formation of the Gaofan Group possibly recorded the GOE; whereas the Mohe-Yaokouqian Formations of the Gaofan Group and the Doucun-Dongye Subgroups of the Hutuo Group recorded the subsequent Lomagundi-Jatuli Event (LJE). However, the Lomagundi-Jatuli carbon excursions are hardly distinguishable from the Gaofan Group and the Doucun Subgroup (Hutuo Group) as both units consist of little inorganic carbon but terrestrial clastic turbidites.